The effect of different surface functionalization of SBA-15 catalysts on the production of C16 bio-aviation fuel precursor - Indri Yati; Feri Mukhayani; Denisa Fitri Salsabila; Irwan Kurnia; Muhammad Al Muttaqii; Amalia Kurnia Amin; Fildzah Adany; Zetryana Puteri Tachrim; Agustina Sus Andreani; Ali H Jawad; Muhammad Ridwan (Center of Biomass & Renewable Energy (CBIORE), 2026)
The increasing global demand for sustainable aviation fuels has driven extensive research on developing efficient heterogeneous catalysts. This study investigates the effect of different surface functionalization methods of mesoporous SBA-15 on its catalytic activity for the production of a C16 precursor of bio-aviation fuel. The SBA-15 surfaces were modified by two acid functionalization routes, namely sulfonation and sulfation, to enhance its surface acidity and catalytic activity. Sulfonation was carried out using 3-mercaptopropyltrimethoxysilane (MPTMS) followed by oxidation to obtain the SO3H–SBA-15 catalyst containing sulfonic acid groups (–SO3H), while sulfation using ammonium sulfate as a precursor produced the SO4–SBA-15 catalyst containing sulfate groups (SO42-). Both catalysts were characterized using NH3-TPD and acid-base titration to quantify the total acidity. The catalytic performance was evaluated through hydroxyalkylation-alkylation (HAA) reaction between 2-methylfuran (2-MF) and methyl isobutyl ketone (MIBK) to synthesize a C16 bio-aviation fuel precursor, 5,5′-(4-methylpentane-2,2-diyl) bis(2-methylfuran) abbreviated as MPM. The results revealed that both modification methods effectively increased the total acid of SBA-15. However, the sulfated SBA-15 catalyst exhibited superior catalytic activity and stronger acid strength than the sulfonated one due to formation of more acid sites on its surface. Therefore, the sulfation route was identified as a more effective strategy for developing highly active solid acid catalysts. This research demonstrates the superior properties of sulfated mesoporous SBA-15 as a promising and sustainable heterogenous catalyst for converting biomass-derived platform chemicals into advanced C16 bio-aviation fuel precursors.